Structure and Description of the Prison Notebooks - Francioni, Gianni (International Gramsci Journal, 2023)
This is an English-language guide to Gramsci’s Prison Notebooks. The original guide (see the previous article) was originally modified and made available in English for an exhibition in Moscow earlier in 2019, in which some of the Notebooks were on show. The English-language version for the Moscow exhibition was more generic in nature than the Italian one on which it was based. The current English version contains integrations from the Italian text to bring it more into line with the original text (see previous article). The guide illustrates the structure of the Notebooks, lists the general contents of each of them and, as far as possible, indicates why given notes are found in given sections of the Notebooks, often special sections set aside on purpose, sometimes with Gramsci’s own titling, for second draftings. Such notebook titles and section sub-titles, if in italics, are Gramsci’s own; otherwise they are later editorial additions. Particular attention is paid to the division between miscellaneous, special and translation notebooks; the article includes the most up-to-date information available on when and where each notebook was written.